Efficiency and Import Penetration on the Productivity of Textile Industry and Textile Products - Rakhmawan, Catur Basuki; Hartono, Djoni; Awirya, Agni Alam (Universitas Prasetiya Mulya, 2012)
Although textile industry and textile products belong to the strategic sub-sector of manufacturing industry in Indonesia, they are facing problems on the availability of energy, old production machines, and the flooding of imported products into the domestic market. This study is aimed to analyze the efficiency and productivity as performance indicators and how the efficiency and import penetration affect the productivity of textile industry and textile products. The methods of data analysis used in this research are divided in two phases. The first phase, the non-metric approach of Data Envelopment Analysis (DEA) is applied to measure the efficiency and productivity. Secondly, the fixed effect model of econometric regression approach is used to find out the effects of efficiency and import penetration on the productivity of textile industry and textile products. The result shows that the average level of efficiency of textile industry and textile products during the period of 2004 – 2008 is about 40 percent with a growth rate of average productivity increases 2.4 percent. Whereas, the econometric estimation results indicate that the increase of efficiency will positively and significantly affect the productivity of textile industry and textile products. On the other hand, the increase of import penetration will negatively affect the productivity of this industry.